Association Between the Inflammatory Biomarkers and Left Ventricular Systolic Dysfunction in Patients with Exacerbations of Chronic Obstructive Pulmonary Disease - Ljiljana Andrijevic; Senka Milutinov; Ilija Andrijevic; Daniela Jokic; Marija Vukoja (Balkan Medical Journal, 2017)
Nearly a quarter of patients with the exacerbation of chronic obstructive pulmonary disease present with left ventricular systolic dysfunction which may be associated with mortality.